THE INFLUENCE OF LEADERSHIP STYLE ON JOB SATISFACTION EMPLOYEES AT ESTOMIHI HOSPITAL MEDAN: PENGARUH GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN PADA RUMAH SAKIT ESTOMIHI MEDAN - Nazara, Asori (UPMI Proceeding Series, 2024)
A hospital is a public sector organization engaged in the field of health services which has the task of carrying out health efforts in an efficient and effective manner by prioritizing or prioritizing healing and recovery efforts which have been carried out in a harmonious and integrated manner by the hospital in an effort to improve and disease prevention and improvement efforts Leadership style has an influence on employees and the company. In an organization, whether in the form of a business organization or a non-business organization, leadership is an important factor that determines the survival or sustainability of the organization. Employee job satisfaction is influenced by the employee's work environment, both the environment between employees and the relationship with management above them. The research method used by researchers based on the research approach above is a quantitative method.